Esophagus Dilation and Quality of Life in Adults with Scleroderma and Concomitant Obstructive Sleep Apnea - KARAKURT, SAİT; DİRESKENELİ, RAFİ HANER (My University, 2024)
(1) Background: Systemic sclerosis (SSc) is a rare systemic disease, which often affects the esophagus, leading to dilation and complications such as dysphagia and reflux. Obstructive sleep apnea (OSA) is a chronic condition with recurrent episodes of upper airway collapsibility and is known to impair quality of life (QoL). The primary aim of this study was to investigate the occurrence of esophagus dilation in patients with SSc and concomitant OSA and, further, to address the impact of these conditions on QoL. (2) Methods: In this cross-sectional cohort study, 62 consecutive patients with SSc underwent chest computer tomography (CT) and home sleep apnea testing. The OSA diagnosis was based on AHI ≥ 15 events/h. The QoL was quantified using the short-form (SF)-36 questionnaire. The patients were dichotomized as high- vs. low-esophageal-diameter groups, based on the median cut-off values. (3) Results: The mean age was 48 ± 11 years; 58 (93.5%) were female; the mean BMI was 26.7 ± 5.0 kg/m2. The median esophageal diameter was 17.47 mm. A larger esophageal diameter was more frequently associated with the diffuse cutaneous subtype of SSc (p = 0.002) and significantly higher Warrick scores (p < 0.001), indicating more severe pulmonary fibrosis. There was a significant linear correlation between the Warrick score and the esophageal diameter (standardized β coefficient 0.544 [%95 confidence interval 0.250–0.609]; p < 0.001). In the subgroup analysis, the patients with both OSA and enlarged esophageal diameter experienced a significant decline in QoL, particularly in the domains of physical functioning, role physical, general health, role emotional, and vitality. (4) Conclusions: While OSA was not directly associated with enlarged esophageal diameter in patients with SSc, those with both OSA and enlarged esophageal diameter exhibited a significant decline in QoL. These findings suggest that the presence of OSA may exacerbate the adverse effects of esophageal dilation on QoL in SSc patients. Our results underline the importance of considering both gastrointestinal and sleep-related aspects in SSc management to enhance patient QoL.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; esophagus dilation; obstructive sleep apnea; quality of life; scleroderma; systemic sclerosis